NACA Ducts in vehicle thermal simulations - Menon, Abhilash (My University, 2017)
NACA ducts are a class of low-drag submerged inlets that find use in aircraft for cooling flows and as engine intakes. Due to their aesthetic appearance and design flexibility, car makers sometimes opt to use NACA ducts for similar applications, especially for high performance vehicles. They are most commonly found on the bonnet or on the side panels. This study concerns NACA ducts located on the under-body of cars, the purpose of which are to provide cooling flows for critical components in the engine bay. The objective was to develop a steady steady state CFD model which can capture the inducted cooling flow and also to assess if this model can be integrated into a “full-car” thermal simulation. A preliminary study was conducted using experimental data, available in literature, for NACA ducts. The information obtained from this was used to simulate underbody ducts on a production car inside a reduced domain which contained parts of the engine bay. Due to the lack of experimental data for the under body ducts, the steady state method was tested against a Large eddy simulation of the reduced domain using identical boundary conditions. The results of the study reveal that a steady state approach can accurately estimate the flow rate through the ducts. The flow immediately downstream of the duct is also captured. However, it’s not accurate enough for the complex flows inside the engine bay, away from the ducts. The study concludes that it would be ill advised to integrate this into a full car simulation as even a slight change in the cooling flow path might lead to erroneous results.
Keywords: Transport; Hållbar utveckling; Strömningsmekanik och akustik; Transport; Sustainable Development; Fluid Mechanics and Acoustics